Pengaruh Model Pembelajaran Project Based Learning terhadap Kemampuan Berfikir Kreatif Siswa pada Mata Pelajaran IPS di SMP Negeri 8 Gorontalo - Yuningsi Husain; Frahmawati Bumulo; Agil Bahsoan; Roy Hasiru; Fatmawaty Damiti (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study aims to determine the influence of the Project Based Learning (PjBL) learning model on students' creative thinking skills in Social Sciences (IPS) subjects at SMP Negeri 8 Gorontalo. Creative thinking skills are one of the 21st century skills that need to be developed in the learning process, especially in social studies lessons that require analysis and solving social problems. This study employed a quantitative approach utilizing primary data from questionnaires distributed to students at SMP Negeri 8 Gorontalo. The sample consisted of 30 respondents, and the data analysis was performed using simple linear regression. The analysis shows that the t-count for the project-based learning model variable is 6.060. To determine whether Ho is confirmed or rejected, the t-table was calculated at a 5% statistical significance level, resulting in a t-table of 1.701. The comparison indicates that the t-count is greater than the t-table. This leads to the rejection of Ho, implying a significant effect of the project-based learning model on students' creative thinking skills.